Effects of MWCNT on Mechanical Properties of Glass-Flax Fiber Reinforced Nano Composites. (2018) - Mohan, K.; Rajmohan, T.
Abstract: In recent years the researchers are more focused on developing green composite materials using different natural fibers which has found their applications in various industries and automobile sectors. It is also holding numerous advantages such as reusability, recyclability and being eco-friendly in nature. The present work deals with the fabrication of Glass and flax fiber hybrid reinforced composites using modified epoxy resin added with Multi walled carbon nano tube (MWCNT) at different Wt% (0%, 0.5%, and 1%) and evaluate the mechanical properties. The compression molding technique is used to prepare the samples and the MWCNT is incorporated into the epoxy resin by using the ultrasonic probe sonicator. The mechanical properties of the composites are obtained by conducting tensile, compression, flexural, impact and hardness tests as per ASTM standards. The morphological characteristics of the composites such as fiber orientation and fracture, bonding between matrix and fiber are revealed by Scanning Electron Microscope (SEM) with Energy Dispersive X-rays (EDS) technique. The X-Ray Diffraction (XRD) technique is used to identify the crystalline species in the composite material. The result shows a significant improvement in the mechanical properties by incorporating the MWCNT.